Eastern and Southern Africa (ESA) consultation on the implementation of the World Bank rural Development strategy. Proceedings of a workshop - International Livestock Research Institute (International Livestock Research Institute, 2003)
This workshop is the third in a series of regional workshops organised by the World Bank. It is conducted to develop and identify mechanisms for improving the empowerment of the rural poor to inform and influence national pro-poor strategy formulation; innovative approaches to scaling up investments in rural Development; mechanisms for improved public-private partnerships in producing international public goods for enhancing rural Development; and mechanisms for improving understanding of the characteristics of the pro-poor implementation process. The Report has three sessions. In session one, two papers are presented on the World Bank rural Development strategy. Session two is on research and technology for poverty reduction - with nine presented papers. Session three is dialogue. Here five issues are discussed as lead presentation as well as round table discussions.